Postoperatorio en rehabilitación oral - Rueda García, Adriana Elizabeth; Olave Bustamante, Gilberto (Revista Estomatología, 1997)
This descriptive study is about the achievement off dental auxiliaries who graduated from the University of Valley of Cali. These dental assistants studied to be either auxiliaries in dental clinics and auxiliaries of oral hygiene in 1991, 1992 and 1993. The sample consisted ofthe information about 52 dental assistants. To analyze the data, two facts were taken into account: the regard expressed by the dentists about their assistants and the regard expressed by the administrators on the same assistants. These assistants, the dentists and the administrators work in public institutions and private dental clinics in Cali. Two kinds ofinstruments were used to get the information. The first one consisted of a writlen questionnaire which was filled out by the dentists and the second was an oral questionnaire answered by the administrators. The results showed favorable approbation which involved good knowledge, skills and human quality. The results will help to propose changes to improve the present programs for dental assistants. Moreover, they will contribute in the design of new courses for the current and continous training.